2018
DOI: 10.15446/dyna.v85n204.65836
|View full text |Cite
|
Sign up to set email alerts
|

Maps of Intrinsic Cost (IC) in reliability problems of medium voltage power distribution systems through a Fuzzy multi-objective model

Abstract: En este trabajo se analizó la fiabilidad de un Sistema de Distribución de Potencia de Media Tensión (SDMT) con la aplicación del Dispositivo de Seccionamiento/Protección (SP). La solución más satisfactoria se obtuvo a través de la metaheurística X-PSO con extensión al dominio difuso. La principal contribución fue la simplificación del índice denominado Costo Intrínseco (IC) y el análisis de los criterios de fiabilidad del coste del dispositivo y de la energía no suministrada. El IC permite obtener la valoració… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…So, the emission mechanisms seek to establish a tax or subsidy, whose price is established by the laws of supply and demand, based on the transaction of property rights. The determination of that price depends on the upper and lower limits and on the preferences of the participating sectors (Camargo et al, 2018). These data are recurrently obtained from statistical analysis, mathematical models and the use of complex models in operations research (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…So, the emission mechanisms seek to establish a tax or subsidy, whose price is established by the laws of supply and demand, based on the transaction of property rights. The determination of that price depends on the upper and lower limits and on the preferences of the participating sectors (Camargo et al, 2018). These data are recurrently obtained from statistical analysis, mathematical models and the use of complex models in operations research (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the important published works are carried out using deterministic models, or in the best of cases, mixed with stochastic models. That is, they use classical models of mathematical programming, which have limitations in their formulation and quality of the results obtained (Camargo et al, 2018;Camargo, 2022b). It is observed that these proposals present complex methods, which require a large amount of data, in some cases require supervised learning and most do not consider the presence of uncertainty, but rather are statistical analyses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations